2013
DOI: 10.5402/2013/671691
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Patient Perspectives about Hypertension

Abstract: To understand hypertensive patients' perspectives regarding blood pressure and hypertension treatment, this qualitative study applied semistructured interviews of hypertensive patients. Participants were recruited from two hypertension clinics at the University of Alberta in Edmonton, Canada. To be eligible for inclusion, patients had to be aged 18 years or older, diagnosed with hypertension by a healthcare provider, and currently taking an antihypertensive medication. Participants were stratified in the analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 33 publications
7
50
0
Order By: Relevance
“…However, implementation of these recommendations is often prone to failure due to various barriers, such as lack of awareness, poor adherence to medication, low motivation for lifestyle changes and lack of family support. A qualitative study on patient perspective of hypertension done in Canada found that patients struggled to define hypertension; only half of them (54%) could recall their targeted blood pressure threshold 12. Other qualitative studies conducted in Malaysia13 and the USA14 reported that their patients were not aware that hypertension could be asymptomatic, and the asymptomatic patients considered themselves healthy.…”
Section: Introductionmentioning
confidence: 99%
“…However, implementation of these recommendations is often prone to failure due to various barriers, such as lack of awareness, poor adherence to medication, low motivation for lifestyle changes and lack of family support. A qualitative study on patient perspective of hypertension done in Canada found that patients struggled to define hypertension; only half of them (54%) could recall their targeted blood pressure threshold 12. Other qualitative studies conducted in Malaysia13 and the USA14 reported that their patients were not aware that hypertension could be asymptomatic, and the asymptomatic patients considered themselves healthy.…”
Section: Introductionmentioning
confidence: 99%
“…47 However, patients reported that enrollment and participation in chronic disease self-management behaviors was complicated by their dependence on family members, 44,50,51 especially those who required informal care and assistance. 45,47,54 Although patients reported that social and emotional support from family and friends was important in facilitating their self-management behaviors, 51 participants also reported poor family support as precluding self-management. 37,44 Some patients believed that asking for assistance with self-management would become a burden on their family and friends.…”
Section: Enabling Factors Social Supportmentioning
confidence: 99%
“…Patients also reported unfavorable attitudes toward enrolling and participating in guided self-management programs due to already high preexisting knowledge of how to best self-manage their own chronic condition. 37,54 However, in two studies, patients living with COPD and hypertension reported several positive attitudes toward participating in self-management programs, including the opportunity to learn more about their condition. 50,52 Patients living with various chronic diseases, including cardiovascular disease, chronic lower respiratory conditions, and type 2 diabetes, reported not enrolling, because self-management programs would not teach them anything new and different from what they already learned from their general practitioner.…”
Section: 49mentioning
confidence: 99%
See 2 more Smart Citations